Quality self-assessment processes in higher education: from an Italian experience to a general tool. Issue 1 (2nd January 2021) - Vesce, E.; Cisi, M.; Gentile, T.; Stura, I.
ABSTRACT: Quality is a multidimensional and transversal concept also in the field of higher education. This and other considerations revealed some problems during application of quality principles to study programmes, emerged from the first accreditation experience in Italy. The objective of this article is to provide a simple self-assessment tool for professors who have to implement study programme quality, in order to understand their position with respect to accreditation requirements. To do this, a general procedure to create the self-evaluation questionnaire is explained. It is composed of six points: (1) studying literature or indications about the objective; (2) creating a schema of categories and sub-categories, (3) weighting the sub-categories, (4) creating a questionnaire, (5) creating a formula in order to synthesise the questionnaire in a graduation scale and finally (6) robustness analysis. A full example, based on Italian experience, is therefore developed in detail.